Association between levodopa administration and melanoma: A systematic review - Luparelli Mello, Fernanda; Estrin, Marcelo Adrian (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Parkinson's disease (PD) is a neurodegenerative disease and levodopa is the main drug used in the treatment of this disease. A study conducted in Denmark demonstrated a two-fold higher incidence of malignant melanoma in patients with Parkinson's, but no correlation was found between levodopa treatment and this incidence. Material and methods: The present systematic review used search engines such as pubmed and Google academic to search for articles of the clinical and randomized trial type. Results: The results of the systematic review indicate a complexity in the relationship between levodopa administration, Parkinson's disease, and melanoma risk. The evidence reviewed suggests that levodopa does not appear to be a significant causal factor in the development of melanoma in patients with Parkinson's disease. Despite the problems raised, the well-established therapeutic benefits of levodopa in the management of the symptoms of Parkinson's disease continue to outweigh the potential risk of causing melanoma. Conclusion: The study concludes that there is an increased risk of developing melanoma in patients with Parkinson's disease but that there is no evidence of a causal role of levodopa in increasing this risk or accelerating its growth